2013
DOI: 10.1163/15736121-12341254
|View full text |Cite
|
Sign up to set email alerts
|

The Semantics of ‘Spirituality’ and Related Self-Identifications: A Comparative Study in Germany and the USA

Abstract: SummaryCulturally different connotations of basic concepts challenge the comparative study of religion. Do persons in Germany or in the United States refer to the same concepts when talking about 'spirituality' and 'religion'? Does it make a difference how they identify themselves? The Bielefeld-Chattanooga Cross-Cultural Study on 'Spirituality' includes a semantic differential approach for the comparison of self-identified "neither religious nor spiritual", "religious", and "spiritual" persons regarding seman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 31 publications
0
25
1
Order By: Relevance
“…The first investigates associations that people have with spirituality, presenting respondents with a predetermined list of characteristics or qualifications that they can endorse or value. Two recent studies of this type are those by La Cour, Hordam Ausker, and Hvidt (2012), and by Keller et al (2013). The second type analyses the definitions of spirituality given by their respondents (Zinnbauer et al, 1997;Gallup and Jones, 2000;Rose, 2001;Marler and Hadaway, 2002;Hodge and McGrew, 2006;Schlehofer, Omoto, and Adelman, 2008;Gall, Malette, and Guirguis-Younger, 2011).…”
Section: Previous Research On Conceptions Of Spiritualitymentioning
confidence: 99%
See 2 more Smart Citations
“…The first investigates associations that people have with spirituality, presenting respondents with a predetermined list of characteristics or qualifications that they can endorse or value. Two recent studies of this type are those by La Cour, Hordam Ausker, and Hvidt (2012), and by Keller et al (2013). The second type analyses the definitions of spirituality given by their respondents (Zinnbauer et al, 1997;Gallup and Jones, 2000;Rose, 2001;Marler and Hadaway, 2002;Hodge and McGrew, 2006;Schlehofer, Omoto, and Adelman, 2008;Gall, Malette, and Guirguis-Younger, 2011).…”
Section: Previous Research On Conceptions Of Spiritualitymentioning
confidence: 99%
“…Interestingly, one of these themes is spirituality understood as selfishness, representative of a negative opinion held by a number of people who endorsed associations such as self-absorbed', and 'egoism'. Using semantic differential questionnaires, Keller et al (2013) showed that both in the United States and Germany spirituality is seen as a much broader term than religion, with generally more positive (or less negative) evaluations. Only in their 'highly religious' groups -people who indicated that they were more 'religious' than 'spiritual' -evaluations of spirituality and religion resembled one another and were both positive.…”
Section: Previous Research On Conceptions Of Spiritualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Within psychology, there have been several published studies on how spirituality as a emic folk category is understood (e.g., Schlehofer et al 2008;la Cour et al 2012;Keller et al 2013), and how it should be conceptualized as a research category (e.g., Zinnbauer et al 1997;1999;Hill et al 2000;Koenig, Harold 2008;Westerink, Herman 2012). The relationship between religion and spirituality, which Herman addresses has been broadly discussed in over a decade within the psychology of religion, but you will not find Pargament, Hill or Koenig mentioned in Herman's analysis.…”
Section: Missing Colleaguesmentioning
confidence: 99%
“…The transformation of traditional religion and the increasing rejection of a materialistic world view have heralded a rise in popular interest regarding spiritual matters over the last four decades. Western society is in the thrall of a 'spiritual revolution' with the emergence of a subjective-life spirituality and concomitant decline of congressional and religious denominations' influence; there is growing empirical evidence that an increasing number of people identify themselves as 'spiritual' but not 'religious' (Zinnbauer 1997;Berghuijis 2013;Keller 2013). Religion is said to be progressively eclipsed by modern spirituality or spiritualities stemming from personal experiences (Heelas 2005).…”
Section: Problematizing the 'European Spiritual Heritage'mentioning
confidence: 99%